PROVIDING BOOKLET MEDIA IN PREVENTING SEXUALLY TRANSMITTED INFECTIONS IN COMMERCIAL SEX WORKERS IN NUSA DUA BALI - dhyana putri (Meditory : The Journal of Medical Laboratory, 2019)
AbstractBackground: Commercial sex workers (CSWs) profession is very vulnerable to various types of sexually transmitted infections (STIs). Providing information of STIs prevention for CSWs is very important so they can recognize the fatal consequences of these STIs. The most practical form or media is booklet because it is easy to understand, and easy to carry anywhere so that they can be aware of the high risk of danger.Objective: The objective of this research is to know the provision of booklet media improvingthe knowledge, attitude, and behavior of CSWs in preventing STIs in the area of South Kuta Health Center Badung regency.Methods:Pre Experiment Research Design with "one group pretest and posttest design" approach with a cross-sectional design. The population in this research is all the CSWs in Nusa Dua Bali. Sampling is accidental sampling. The number of samples taken 25% of the population so that the amounts of samples is 100 people.Results: Respondent average age in the range of 18-27 years (42%), Education Level of elementary school (48%), length of work (47%) marital status that is married/divorce (69%). From Kolmogorov Smirnov test result on 6 variables such as pre and posttest knowledge, pre and posttest attitude and pre and posttest behavior variable, the pretest attitude variable has the normal distribution with signification 0,218 while the other variable is the not normal distribution with signification less than 0.000. Wilcoxon test results obtained significance for the variable knowledge, attitude and behavior of 0,000 smaller than 0.05 indicates there is a difference of average score of knowledge, attitude and behavior before and after given booklet media.Conclusion: Knowledge and understanding of a person will affect the attitude, then affect the intention of someone's to perform the action or behave. It can be interpreted that person’s education level affects attitude and behavior in life. Booklet  improving the knowledge, attitudes, and behavior of CSWs in preventing STIs in Nusa Dua Bali